Neural stem cells-derived neurons obtained from human pluripotent stem cells as an in vitro model for studying CDK5/p25 mediated neurodegenerative processes - Mucci, Sofia (2020)
Human embryonic and induced pluripotent stem cells (hESCs and IPSCs)can differentiate into a wide range of specialized cells,including neural stem cells (NSC). Moreover, NSC-derived neurons are proposed as a model for studying neurodegeneration. CDK5/ p35 complex is involved in neuronal homeostasis and development. However, its functionis deregulated in neurodegeneration by p35 cleavage in p25, which allows the aberrant phosphorylation of targets through the constitution of a more stable complex CDK5/p25. In this work we aimed to set up an in vitroCDK5/p25 neurodegenerative model using NSC-derived neurons obtained from hESCs and hIPSCs subjected to different cellular stressors. For this purpose, we first derived NSC from hESC (H9 line) and hIPSC (FN 2.1 line), which were further differentiated into neuronsusin a neural induction kit. NSC and neuron-like phenotype were validated by immunofluoresce and RT-qPCR of cell specific markers (sox-1, Sox-2, pax-6 and nestin for NSC; MAP5, MAP2 and Tuj-1 for neurons). Then, CDK5 and p35 mRNA and protein expression levels were analyzed in hESCs, hIPSCs, NSC and neurons by RT-qPCR and western blot. Interestingly, we observed that althought CDK5 was ubiquitous, p35 mRNA and protein were mainly expressed in neurons. We next evaluated how different stress stimuli (rotenone, glutamate and calcium ionophore A23187) affected NSC andneurons viability. We determined the percentage of cell viability after 24 hours treatment with increasing concentrations of rotenone and glutamate and 2 hours treatment with A23187 using an XTT vital dye assay. Cell viability felt downsignificantly in the case of rotenone and A23187 treatments in a concetration dependent manner. In conclusion, NSC-derived neurons obtained from hESCs andhiPSCs expressed high levels of p35 and responded to rotenone stressor, making them a suitable CDK5/p25 neurodegenerative invitro model.